2012
DOI: 10.1089/cyber.2012.0207
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Among Primary School Students in Turkey: Self-Reported Prevalence and Associations with Home and School Life

Abstract: The current study examined the self-reported prevalence and nature of cyberbullying and victimization among second, third, and fourth grade students (N=372) and explored associated features of home and school life. Of the children in the current sample, 27 percent had been victims of cyberbullying, 18 percent had been aggressors, and 15 percent had been both cyberbullies and victims. Boys were significantly more likely to carry out cyberbullying than girls. Cyberbullying exposure (as both a bully and a victim)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 32 publications
8
38
1
5
Order By: Relevance
“…Yapılan araştırmalar siber zorbalık ve mağduriyet ile cinsiyet, yaş (Ayas ve Horzum, 2012;Hinduja ve Patchin, 2010;Peker ve Eroğlu, 2013;Peker, Eroğlu ve Çitemel, 2012), ailenin aylık geliri (Arslan, Savaşer, Hallett ve Balcı, 2012), anne ve babanın eğitim düzeyi, anne ve babanın birlikte yaşama durumu (Mitchell, Finkelhor ve Wolak, 2003), internete bağlanılan yer (Akbulut, Şahin ve Erişti, 2010), internet kafeye gitme sıklığı (Akbulut ve Erişti, 2011), internetin aşırı kullanımı , bilgisayar kullanma becerisi (Ybarra ve Mitchell, 2004), ergenin anne ve babasının bilgisayar becerisine ilişkin algısı, interneti kullanma amaçları (Akbulut ve diğerleri, 2010), ebeveyn ve okul personelinin denetimi (Kabalcıoğlu ve Eroğlu, 2013;Spears, Slee, Owens ve Johnson, 2008), filtre programı kullanma (Eroğlu, 2014;Mitchell, Finkelhor ve Wolak, 2005) ve sosyal paylaşım sitelerini kullanma sıklığı (O'Dea ve Campbell, 2012) arasında anlamlı ilişkiler bulunduğunu rapor etmişlerdir.…”
unclassified
“…Yapılan araştırmalar siber zorbalık ve mağduriyet ile cinsiyet, yaş (Ayas ve Horzum, 2012;Hinduja ve Patchin, 2010;Peker ve Eroğlu, 2013;Peker, Eroğlu ve Çitemel, 2012), ailenin aylık geliri (Arslan, Savaşer, Hallett ve Balcı, 2012), anne ve babanın eğitim düzeyi, anne ve babanın birlikte yaşama durumu (Mitchell, Finkelhor ve Wolak, 2003), internete bağlanılan yer (Akbulut, Şahin ve Erişti, 2010), internet kafeye gitme sıklığı (Akbulut ve Erişti, 2011), internetin aşırı kullanımı , bilgisayar kullanma becerisi (Ybarra ve Mitchell, 2004), ergenin anne ve babasının bilgisayar becerisine ilişkin algısı, interneti kullanma amaçları (Akbulut ve diğerleri, 2010), ebeveyn ve okul personelinin denetimi (Kabalcıoğlu ve Eroğlu, 2013;Spears, Slee, Owens ve Johnson, 2008), filtre programı kullanma (Eroğlu, 2014;Mitchell, Finkelhor ve Wolak, 2005) ve sosyal paylaşım sitelerini kullanma sıklığı (O'Dea ve Campbell, 2012) arasında anlamlı ilişkiler bulunduğunu rapor etmişlerdir.…”
unclassified
“…Twenty-nine of the studies consisted only of multiple choice and/or Likert scales questions. This method can result in acquiescence bias, where participants are more likely to agree with statements, or indicate positively, and it also limits respondents to choose from the posed responses rather than inviting general statements of opinion or replies [46]. Given the age of the children involved in these studies, the role of using open-ended questions or open dialogue/interviews to determine their knowledge and experiences needs greater consideration, as studies into bullying have revealed that young children often confuse terms and understandings [62].…”
Section: Overview Of Methodologies Employedmentioning
confidence: 99%
“…Individual interviews allow the researcher to investigate children's experiences confidentially, which is particularly beneficial when "researching sensitive or personal issues" [83], such as cyberbullying. Face-to-face interviews are, however, resource intensive [46], particularly for large studies, where additional staff may need to be employed and trained in interview protocols.…”
Section: Using Dialogue To Research With Young Childrenmentioning
confidence: 99%
“…Additionally, over 50 percent of Polish teenagers and 34 percent of English and Belgian adolescents have faced cyberbullying in some form (European Law Monitor, ). One study of second‐, third‐, and fourth‐grade children in Turkey found that 27 percent had been victimized through cyberbullying (Arslan, Savaser, Hallett, & Balci, ) while another study of high school students in Central China found that over half had been cyberbullied (Zhou et al, ). Indeed, the issue has drawn similar attention in Europe as it has in the United States—the European Commission itself is approaching the problem by way of its “Safer Internet Campaign, which is essentially a public awareness campaign for teenagers, providing advice and strategies to mitigate the harms of cyberbullying” (Zhou et al, ).…”
Section: International Approachesmentioning
confidence: 99%